Analysis of the global origin, evolution and transmission dynamics of the emerging novel variant IBDV (A2dB1b): The accumulation of critical aa‐residue mutations and commercial trade contributes to the emergence and transmission of novel variants. Issue 5 (30th June 2022) - Wang, Weiwei; He, Xiumiao; Zhang, Yan; Qiao, Yuanzheng; Shi, Jun; Chen, Rui; Chen, Jinnan; Xiang, Yanhua; Wang, Zhiyuan; Chen, Guo; Huang, Jianni; Huang, Teng; et al.
Abstract: The Chinese IBDV novel variant (nvIBDV), belonging to the genotype A2dB1b, an emerging pathotype that can cause subclinical disease with severe, prolonged immunosuppression, poses a new threat to the poultry industry. The process of the global origin, evolution and transmission dynamics of nvIBDV, however, is poorly understood. In this study, phylogenetic trees, site substitutions of amino acid (aa) and highly accurate protein structure modelling, selection pressure, evolutionary and transmission dynamics of nvIBDV were analysed. Interestingly, nvIBDV was classified into the same genogroup with the early US antigenic variants (avIBDV) but in a new lineage with a markedly different and specific pattern of 17 aa‐residual substitutions: 13 in VP2 (77D, 213N, 221K, 222T, 249K, 252I, 253Q, 254N, 284A, 286I, 299S, 318D and 323E) and four in VP1 (141I, 163V, 240E and 508K). Importantly, the aa‐residues 299S and 163V may play a key role in cell binding and polymerase activity, respectively. The effective population size of the circulating avIBDV experienced two growth phases, respectively, in the years 1999–2007 (in North America) and 2015–2021 (in Asia), which is consistent with the observed trend of the epidemic outbreaks. The most recent common ancestor (tMRCA) of avIBDV most first originated in the USA and was dated around the 1970s. After its emergence, the ancestor virus of this group probably spread to China around the 1990s and the variants experienced a long‐term latent circulation with the accumulation of several critical aa‐residue mutations in VP2 until re‐emerging in 2016. At present, central China has become the epicentre of nvIBDV spread to other parts of China and Asian countries. Importantly, a strong correlation seems to exist between the transmission patterns of virus and the flow of commercial trade of live poultry and products. These findings provide important insights into the origin, evolution and transmission of the nvIBDV and will assist in the development of programs for control strategies for these emerging viruses.